Effect of gas properties and pore pressure on the microcrack propagation in coal - WANG Dengke; PANG Xiaofei; WEI Jianping; ZHANG Hongtu; YAO Banghua; WEI Le; GUO Yujie; YUAN Mingyu; TANG Jiahao (Meitan kexue jishu, 2023)
Using an industrial CT scanning system, we observed the characteristics of micro-fracture Generation and expansion in coal under different gas pressure conditions, providing a new basis for revealing the factors controlling the gas flow output of coal seams. The results of the test analysis showed that: under the action of non-adsorbed gas, the growth rate of fracture volume and fracture area percentage decreases gradually as the pore pressure increases and the sprouting and expansion of microfractures inside coal becomes more obvious. Fracture expansion equation under the influence of pore pressure is satisfied; microfracture extension is mainly controlled by stress concentration effect and coal matrix shrinkage effect. Under the action of adsorptive gas, with the extension of adsorption time, generation and expansion in coal of micro fissures become more and more significant until the expansion equilibrium; the growth rate of fissure volume and fissure area percentage then gradually becomes smaller, in line with the fissure expansion equation under the influence of adsorption time; the fracture extension is mainly affected by stress concentration effect, coal matrix shrinkage effect, erosion effect and deterioration mechanism. The larger the adsorption pressure the longer the adsorption equilibrium time required for the coal; the micro fissure expansion equilibrium time is longer than the gas adsorption equilibrium time, and the fissure expansion has obvious hysteresis.